Effect of dietary supplements in American bullfrogs reared in low and high stocking densities - Freitas, Jorgina Juliana Gradisse; Viau, Priscila; Oliviera, Claudio Alvarenga; Teixeira, Patricia Coelho; Tachibana, Leonardo; de Carla Dias, Danielle; Hipolito, Marcio; Bordon, Isabella Cristina C. [UNESP]; Alfaia, Sthefany Rosa; Ferreira, Claudia Maris (Elsevier, 2017)
The aim of this study was to evaluate the effect of the probiotic Bacillus subtillis and beta-glucan from the fungus Agaricus blazei on survival, growth and immunological capacity in bullfrogs (Lithobates catesbeianus) cultured in low and high stocking densities. Animals weighing 24.3 ± 2.38 g were randomly distributed into four treatments with four simultaneous replicates: D100: 100 frogs/m2 (control); D236: 236 frogs/m2; D236 + Prob.: 236 frogs/m2 supplemented with probiotic; and D236 + BG: 236 frogs/m2 supplemented with beta-glucan. The parameters evaluated were weight gain, survival, plasma corticosterone (CORT), phagocytic capacity (PC) and phagocytic index (PI), at 24 h and 15 and 30 days. There is significant interaction between treatments and time for CORT levels. At 30 days, these values were very close for the D100 (control) and D236 + BG groups. Meanwhile, no statistical differences were observed between treatments for PC and PI. These results indicate that beta-glucan reduced the effects of stress caused by high density in bullfrogs, but the probiotic did not reduce these effects. Both compounds are not efficient at increasing survival rates, weight gain and neither immune response of animals. Thus, the use of commercial food additives may not have the favorable impact desired by the farmer. Their use in aquaculture should be further studied in experiments involving a longer trial period and taking into account the cost of their use.
Keywords: Beta-glucan; Corticosterone; Immune response; Lithobates catesbeianus; Probiotic